Oral manifestations and their management in children undergoing haemodialysis treatment - Pertiwi, Arlette Suzy Puspa; Sasmita, Inne Suherna; Gartika, Meirina (Padjadjaran Journal of Dentistry, 2007)
Haemodialysis is a medical procedure that artificially filters blood. This procedure is carried out to treat children with end-stage renal disease (ESRD). Although haemodialysis is a lifesaving treatment, it also raises many severe oral manifestations associated with ESDR. Among these are increased hypoplasia, enamel opacities, uremic stomatitis, oral bleeding, increased periodontal disease, reduced salivary flow, xerostomia, and an increased tendency of calculus deposition. This paper will discuss the oral manifestations associated with ESRD and their management in children undergoing haemodialysis treatment.